Validation of a High-Throughput Multiplex Genetic Detection System for Helicobacter pylori Identification, Quantification, Virulence, and Resistance Analysis - Zhang, Yanmei; Zhao, Fuju; Kong, Mimi; Wang, Shiwen; Nan, Li; Hu, Binjie; Olszewski, Michal A.; Miao, Yingxin; Ji, Danian; Jiang, Wenrong; Fang, Yi; Zhang, Jinghao; et al. (Frontiers in Microbiology, 2016)
Helicobacter pylori (H. pylori) infection is closely related to various gastroduodenal diseases. Virulence factors and bacterial load of H. pylori are associated with clinical outcomes, and drug-resistance severely impacts the clinical efficacy of eradication treatment. Existing detection methods are low-throughput, time-consuming and labor intensive. Therefore, a rapid and high-throughput method is needed for clinical diagnosis, treatment and monitoring for H. pylori. HMGS assay was established to simultaneously detect and analyze a set of genes for H. pylori identification, quantification, virulence, and drug resistance by optimizing the singlet-PCR and multiple primers assay. Twenty-one pairs of chimeric primers consisted of conserved and specific gene sequences of H. pylori tagged with universal sequence at the 5’ end were designed. Singlet-PCR assay and multiple primers assay were developed to optimize the High-throughput Multiplex Genetic Detection System (HMGS). The specificity of HMGS assay was evaluated using standard H. pylori strains and bacterial controls. Six clinical isolates with known genetic background of target genes were detected to assess the accuracy of HMGS assay. Artificial mixed pathogen DNA templates were used to evaluate the ability to distinguish mixed infections using HMGS assay. Furthermore, gastric biopsy specimens with corresponding isolated strains were used to assess the capability of HMGS assay in detecting biopsy specimens directly. HMGS assay was specific for H. pylori identification. HMGS assay for H. pylori target genes detection were completely consistent with the corresponding genetic background. Mixed infection with different drug-resistant isolates of H. pylori could be distinguished by HMGS assay. HMGS assay could efficiently diagnose H. pylori infection in gastric biopsy specimens directly. HMGS assay is a rapid and high throughput method for the simultaneous identification and quantification of H. pylori, analysis of virulence and drug resistance in both isolated strains and biopsy specimens. It could also be used to distinguish the mixed infection with different resistant genotype strains. Furthermore, HMGS could detect H. pylori infection in gastric biopsy specimens directly.